Analisis Semiotika Roland Barthes pada Sinetron “Beri Cinta Waktu” Episode 50 Karya Anika Maharani - Nafisah, Zambia Dian (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study analyzes the denotative, connotative, and mythic meanings contained in the television drama “Beri Cinta Waktu” episode 50 by applying Roland Barthes’ semiotic framework. The research focuses on seven selected scenes that are considered representative in conveying narrative and symbolic messages within the storyline. Using a qualitative descriptive approach, this study examines both visual and verbal signs, including dialogue, facial expressions, body language, camera angles, and setting, to reveal how meaning is constructed and communicated to the audience. The findings show that at the denotative level, the scenes portray everyday reality and observable actions as they appear on screen. At the connotative level, deeper meanings emerge, reflecting emotions, interpersonal relationships, power dynamics, and prevailing cultural norms. Meanwhile, at the mythic level, the drama reproduces broader ideological constructions, such as societal perceptions of love, jealousy, age hierarchy, and culturally embedded practices that are often taken for granted. These results indicate that “Beri Cinta Waktu” functions not merely as a form of entertainment, but also as a cultural text that actively reproduces and reinforces social values and dominant viewpoints, thereby shaping the audience’s understanding and interpretation of social reality